Green Mussel Biofilter System in Vannamei Shrimp Farming - Yushra Yushra; Andi Adam Malik; Sahabuddin Sahabuddin; Muh. Iqbal Quraisyin (Institute of Advanced Knowledge and Science, 2024)
Vannamei shrimp (Litopenaeus vannamei) farming in Pinrang Regency faces various challenges, including high mortality rates, slow growth, and attacks by various diseases, which are largely caused by poor water quality. This study aims to assess the potential of using green mussels (Perna viridis) as a biofilter to improve water quality and, in turn, enhance shrimp farming productivity. The research was conducted in Suppa District, using shrimp ponds managed with a traditional system and equipped with water reservoirs. Green mussels were used in the biofiltration system to improve water quality. The results showed that the use of green mussels significantly reduced the concentration of heavy metals such as mercury (Hg), copper (Cu), cadmium (Cd), lead (Pb), and zinc (Zn) in the pond water. This improvement in water quality contributed to an increase in shrimp production to 582 kg/ha, a significant rise compared to the previous production level of 250 kg/ha and the national average of 500 kg/ha. The biofiltration process by green mussels helped reduce pollutants and created a healthier environment for shrimp growth. These findings suggest that using green mussels as a biofilter can effectively improve water quality and Vannamei shrimp farming productivity, while providing an environmentally friendly solution to enhance production yields in the shrimp farming industry in the region.